Comprehensive characterization of tissue-specific circular RNAs in the human and mouse genomes. (20th August 2016) - Xia, Siyu; Feng, Jing; Lei, Lijun; Hu, Jun; Xia, Linjian; Wang, Jun; Xiang, Yu; Liu, Lingjun; Zhong, Shan; Han, Leng; He, Chunjiang
Abstract: Circular RNA (circRNA) is a group of RNA family generated by RNA circularization, which was discovered ubiquitously across different species and tissues. However, there is no global view of tissue specificity for circRNAs to date. Here we performed the comprehensive analysis to characterize the features of human and mouse tissue-specific (TS) circRNAs. We identified in total 302 853 TS circRNAs in the human and mouse genome, and showed that the brain has the highest abundance of TS circRNAs. We further confirmed the existence of circRNAs by reverse transcription polymerase chain reaction (RT-PCR). We also characterized the genomic location and conservation of these TS circRNAs and showed that the majority of TS circRNAs are generated from exonic regions. To further understand the potential functions of TS circRNAs, we identified microRNAs and RNA binding protein, which might bind to TS circRNAs. This process suggested their involvement in development and organ differentiation. Finally, we constructed an integrated database TSCD (T issue-S pecific C ircRNA D atabase: http://gb.whu.edu.cn/TSCD ) to deposit the features of TS circRNAs. This study is the first comprehensive view of TS circRNAs in human and mouse, which shed light on circRNA functions in organ development and disorders.